A d10 Ag(i) amine–borane σ-complex and comparison with a d8 Rh(i) analogue: structures on the η1 to η2:η2 continuum. Issue 26 (23rd April 2019) - Johnson, Alice; Martínez-Martínez, Antonio J.; Macgregor, Stuart A.; Weller, Andrew S.
Abstract : The bonding in H3 B·NMe3 σ-complexes of d 8 -Rh(i ) and d 10 -Ag(i ) show subtle differences, as probed by structural, spectroscopic and computational studies. Abstract : H3 B·NMe3 σ-complexes of d 8 [(L1 )Rh][BAr F 4 ] and d 10 [(L1 )Ag][BAr F 4 ] (whereL1 = 2, 6-bis-[1-(2, 6-diisopropylphenylimino)ethyl]pyridine) have been prepared and structurally characterised. Analysis of the molecular and electronic structures reveal important but subtle differences in the nature of the bonding in these σ-complexes, which differ only by the identity of the metal centre and the d-electron count. With Rh the amine–borane binds in an η 2 :η 2 fashion, whereas at Ag the unsymmetrical Ag⋯H3 B·NMe3 unit suggests a structure lying between the η 2 :η 2 and η 1 extremes.